2014
DOI: 10.1016/j.meegid.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus genotypes in Belarus, 2008–2012

Abstract: This study describes group A rotavirus (RVA) genotype prevalence in Belarus from 2008–2012. In 2008, data from 3 sites in Belarus (Brest, Mogilev, Minsk) indicated that G4P[8] was the predominant genotype. Data from Minsk (2008–2012) showed that G4P[8] was the predominant RVA genotype in all years except in 2011 when G3P[8] was most frequently detected. Other RVA genotypes common in Europe (G1P[8], G2P[4]) were detected each year of the study. This study reveals the dominance of genotype G4P[8] in Belarus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In Republic of Korea, the most common genotypes were G1P(8), G2P(4) and G9P (8) in the study published by Kim et al [1], while Boula et al [15] reported G9P(8), G1P(8) and G3P(6) genotypes in Cameroon. In contrast, Semeiko et al [16] found the G4P(8) as the predominant genotype in Belarus.…”
Section: Discussionmentioning
confidence: 85%
“…In Republic of Korea, the most common genotypes were G1P(8), G2P(4) and G9P (8) in the study published by Kim et al [1], while Boula et al [15] reported G9P(8), G1P(8) and G3P(6) genotypes in Cameroon. In contrast, Semeiko et al [16] found the G4P(8) as the predominant genotype in Belarus.…”
Section: Discussionmentioning
confidence: 85%